Verbal estimates in The Holy Quran and their impact on deriving Fiqh rulings related to worship - Al-Ghdarj, Ahmed Abdo Ahmed (Arab Journal for Sciences and Research Publishing, 2023)
This research aims to Identify verbal assessments in the Holy Qur’an, and their Impact on deriving jurisprudential rulings related to worship, with regard to assessments In terms of definition, related terms, and a statement of their importance and benefits, as well as In terms of their impact on deriving jurisprudential rulings related to worship. The researcher used the descriptive and deductive approaches, and he collected the verses that contain verbal assessments related to worship and chose models from them, then he explained the apparent ruling in the verses, then between the hidden ruling derived from the assessment in the verses, then he mentioned the sayings of the jurists In that, and the weighting In the dispute, and reached The researcher then reached the most important result: 1- One of the benefits of verbal assessments is the elicitation of background jurisprudential rulings، and access to the Sharia ruling. 2-Ulama differ in their understanding of verbal estimations، so sometimes they agreed on the necessity of these in the Qur’anic verses، and what follows from them. From. reaching a legal ruling، and sometimes they differed. Turn، as well as my evidence. 3-The علماء used to appreciate the Qur’anic verses. To support their doctrines and jurisprudential views، we find the Hanafi estimate As well as Al-Shafi’I، Al-Hanbali، and perhaps they agreed on one estimate and differed on another، and perhaps. some of them separated from the other. 4- the Arabic sentence was not obscured by the meaning، it was necessary to appreciate it; To show those signs hidden under the structures The phenomenon، highlighting it، showing it، and revealing it. Appreciating the diversity of the meanings of the Arabic sentence، and its implications.